Density functional study of optical properties of beryllium chalcogenides compounds in nickel arsenide B8 structure - Yarub, Al - Douri; Baaziz, H.; Charifi, Z.; Ali Hussain, Reshak, Prof. Dr. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/